2013
DOI: 10.5539/ijbm.v8n11p76
|View full text |Cite
|
Sign up to set email alerts
|

The Shareholders Confidence and Effectiveness of the Joint Auditors: Empirical Validation in the French Context

Abstract: The goal of our research work is to show the effect of the presence of joint auditors (BIG4) and a few mechanisms of governance on the shareholders' confidence. We are trying to explore the relationship between its different variables in the French context during the period 2005-2010.The empirical results show a positive and significant relationship between, on the one hand, the presence of two auditors BIG4, the opinion of the auditors, the independence of the members of the audit committees and the boards of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…In such case, the joint audit will be more effective without an increase in cost as compared with employing single audit partners, when they are located in different audit offices, audit will be more efficient as cost will decrease slightly without a sacrifice in audit quality [38]. Finally, joint audit has a positive impact on shareholders' confidence [39] and a negative impact on the cost of equity and the implied cost of equity; however the investors' perception of the joint audit has been significantly mitigated if one of the two appointed auditors is a non-big 4 auditor [40]. To investigate the impact of joint audit from the investors' point of view in a developing country, Alfraih tested the effect of three pairs of auditors (two big 4, one big 4 and one non-big 4, and two non-big 4 audit firms) on firm value as measured by the value relevance of accounting information (earnings and book value) [41].…”
Section: Joint Audit Scenariomentioning
confidence: 99%
“…In such case, the joint audit will be more effective without an increase in cost as compared with employing single audit partners, when they are located in different audit offices, audit will be more efficient as cost will decrease slightly without a sacrifice in audit quality [38]. Finally, joint audit has a positive impact on shareholders' confidence [39] and a negative impact on the cost of equity and the implied cost of equity; however the investors' perception of the joint audit has been significantly mitigated if one of the two appointed auditors is a non-big 4 auditor [40]. To investigate the impact of joint audit from the investors' point of view in a developing country, Alfraih tested the effect of three pairs of auditors (two big 4, one big 4 and one non-big 4, and two non-big 4 audit firms) on firm value as measured by the value relevance of accounting information (earnings and book value) [41].…”
Section: Joint Audit Scenariomentioning
confidence: 99%
“…Second: Studies that found that joint audit has positive effect on audit quality (Baldauf & Steckel, 2012;Zerni et al, 2012;Benali, 2013;Ittonen & Tronnes, 2015;Relvas & Pais, 2015). Most of these studies examined the impact of voluntary joint audit on audit quality.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In a case study conducted by (Baldauf & Steckel, 2012) to investigate whether joint audit, as opposed to single audit, improves the degrees of auditor's report consensus and accuracy, as proxies of audit quality, (Baldauf & Steckel, 2012) found that audit reports issued by auditors involved in joint audit process are more conservative and more accurate than that issued by auditors involved in single audit process, as the communication between auditors involved in joint audit process and the discussion of audit findings between them improves the accuracy of audit opinion expressed, thus enhancing the level of audit quality. Furthermore, (Benali, 2013) examined the effect of joint audit on shareholders' confidence of joint auditors, and found that, with a sample of 145 French listed companies during the period 2005 through 2010, the use of joint auditors, especially two big-4 auditors, by French listed companies has a positive and significant impact on the shareholders' confidence. In the same context, (Relvas & Pais, 2015) investigated the impact of joint audit on cost of debt, as a proxy for audit quality.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the premise of agency theory, it is believed that the new regulatory attempt (MCCG, 2012) or tuning up of the recommendations of the previous code (MCCG, 2007) regarding independence of Malaysian boards will assist firms in ensuring good governance and improving monitoring and advising of their management. Also, it is believed that these, in turn, will improve the confidence of shareholders and firms' market performance reflected by an increase in share market price (Baker and Anderson, 2010;Benali, 2013;Lama, 2013). However, these projections regarding the new code are mere expectations as its recommendations have rarely been empirically investigated in the past.…”
Section: Introductionmentioning
confidence: 99%